BROWN NOISE, PENDEKATAN INSTRUMENTASI DAN POST PRODUKSI “MUSIK TERAPI UNTUK ADHD DEWASA”: SEBUAH TAWARAN - Murwaningrum, Dyah; Fausta, Ega; Ginanjar, Moch. Gigin (Paraguna, 2023)
The issues of mental health have become increasingly prevalent in recent times. People are exploring therapeutic methods from various avenues, including musik. Unfortunately, the availability of musik therapy is limited. This research aims to provide insight into how brown noise is closely related to musik that is considered to have a positive impact on adult ADHD survivor. The brown noise indicator (slope) can be one of measures in instrument selection. This research aims to explain the spectral sound characteristics trend in some musik therapies designed for adult ADHD survivor. This study uses noise-based approach in analyzing and finding the conclusion. The research process begins with sample selection, the determination of the main sample, analyze and measure the sample using deep listening and visual monitoring methods. The tools used are DAW Studio one 6.5, Spectrum meter plug in, and Ayaic CoS 6 Pro. The result of this research consisting of patterns in ADHD musik therapy measured through a noise approach, including white noise, pink noise and brown noise. The findings of this study are expected to assist musik therapy creator in instrument selection.